2016
DOI: 10.1002/alr.21840
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pituitary resection: characterizing surgical approaches and complications

Abstract: A greater proportion of children undergo transfrontal approaches for pituitary lesions than in their adult counterparts. This difference may harbor a potential to influence future sellar resection approaches in children toward a transsphenoidal operation when surgically feasible. Patients undergoing transfrontal procedures have greater risks for many intraoperative and postoperative complications relative to individuals undergoing transsphenoidal resections. Among patients undergoing transsphenoidal approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Our study, utilizing the 2009 and 2012 databases, represents a comprehensive analysis with one coding scheme (ICD‐9). Several recent publications have used the KID in a similar manner to characterize other pediatric conditions …”
Section: Methodsmentioning
confidence: 99%
“…Our study, utilizing the 2009 and 2012 databases, represents a comprehensive analysis with one coding scheme (ICD‐9). Several recent publications have used the KID in a similar manner to characterize other pediatric conditions …”
Section: Methodsmentioning
confidence: 99%
“…10 Not only were these complication rates lower than their transfrontal counterparts but transsphenoidal patients also had a shorter LOS and total cost. 10 With the support of these data, it is not surprising that pediatric skull base centers have followed suit with widespread adoption of TSPR; however, data on image guidance are still lacking in this population. This is the first study that demonstrates the increasing utilization of image guidance in pediatric TSPR cases.…”
Section: Discussionmentioning
confidence: 97%
“…This is a consequence of the infrequency of pediatric pituitary lesions, low necessity for surgery, and that the traditional transcranial approach is still more frequently performed than in adults. 10,12 Pediatric TSPR data are mostly limited to two larger case series and one population-based analysis. Jane et al studied 22 pediatric craniopharyngioma patients who underwent transsphenoidal resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual changes (6.4%), CSF leak (2.3%), and intracranial bleeding (2.1%) are also uncommonly seen complications in pediatric adenoma management . Hanba et al revealed higher complication rates in patients under 10 years of age, with increased incidence of DI, hydrocephalus, and panhypopituitarism in younger patients . The most typical surgical indication for adenomas in children is symptoms related to hormonal secretion as opposed to macroadenomas with optic nerve compression as seen in adults .…”
Section: Discussionmentioning
confidence: 99%